1984
DOI: 10.1203/00006450-198411000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Dysrhythmias after Congenital Heart Surgery: a Canine Model

Abstract: ABSTRACT. To examine the possible mechanisms of ventricular dysrhythmias in the presence of right ventricular hypertension and following ventriculotomy, we instrumented 6-month-old puppies. There were four groups: 1) six animals served as controls (instrumentation only); 2) six animals underwent ventriculotomy only; 3) six animals underwent pulmonary artery banding with a pneumatic vessel occluder to produce right ventricular hypertension; 4) six animals had both ventriculotomy and right ventricular hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Our observations also help to delineate the contribution made by PR to arrhythmia. Although a previous animal model of chronic RV outflow tract obstruction and ventriculotomy (34) suggested that triggered mechanisms may be the predominant mechanism of tachycardia in patients after congenital heart surgery, the presence of frequent and complex automatic ventricular activity failed to predict clinically important ventricular arrhythmia or sudden death in at least two large clinical studies (4,35). Our data emphasize the potential contribution of chronic PR to the development of reentry arrhythmia.…”
Section: Pulmonary Regurgitation and Arrhythmiamentioning
confidence: 69%
“…Our observations also help to delineate the contribution made by PR to arrhythmia. Although a previous animal model of chronic RV outflow tract obstruction and ventriculotomy (34) suggested that triggered mechanisms may be the predominant mechanism of tachycardia in patients after congenital heart surgery, the presence of frequent and complex automatic ventricular activity failed to predict clinically important ventricular arrhythmia or sudden death in at least two large clinical studies (4,35). Our data emphasize the potential contribution of chronic PR to the development of reentry arrhythmia.…”
Section: Pulmonary Regurgitation and Arrhythmiamentioning
confidence: 69%
“…[5][6][7][8][9] Former studies suggest that fibrosis could be the cause of right ventricular dysfunction and arrhythmias, 10,11 and myocardial fibrosis has been demonstrated in patients after repair and in animal models of tetralogy of Fallot. 12,13 Delayed enhancement cardiac MRI has been established as a reliable tool to visualise myocardial necrosis and scar in clinical practice with modern phasesensitive inversion recovery sequences providing consistently high-quality images for both ventricles. 14 The aim of this study was to reliably detect or exclude myocardial scars of the right and left ventricles after complete repair of tetralogy of Fallot using phase-sensitive inversion recovery delayed enhancement imaging.…”
Section: T Etralogy Of Fallot Is the Most Commonmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Several potential substrates and possible mechanisms for ventricular arrhythmia exist, such as hypertrophy, dilatation, delayed intraventricular conduction due to bundle branch block, and surgical scars. 11,13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] VEBs and nonsustained ventricular tachycardia occur in up to 50% of patients 9,12,15,16,[32][33][34][35] and a correlation with prognosis has been implied in some, [10][11][12][13][14][15]32 but not in other reports. 16,19,33 Ventricular arrhythmias have been approached by invasive electrophysiological techniques with [25][26][27]36,37 or wi...…”
mentioning
confidence: 99%